A prospective study of etiology of childhood acute bacterial meningitis, Turkey - Ceyhan, Mehmet; Yildirim, Inci; Balmer, Paul; Borrow, Ray; Dikici, Bunyamin; Turgut, Mehmet; Gray, Steve (Centers Disease Control & Prevention, 2008)
Determination of the etiology of bacterial meningitis and estimating cost of disease are important in guiding vaccination policies. To determine the incidence and etiology of meningitis in Turkey, cerebrospinal fluid (CSF) samples were obtained prospectively from children (1 month-17 years of age) with a clinical diagnosis of acute bacterial meningitis. Multiplex PCR was used to detect DNA evidence of Streptococcus pneumoniae, Haemophilus influenzae type b (Hib), and Neisseria meningitidis. In total, 408 CSF samples were collected, and bacterial etiology was determined in 243 cases; N. meningitidis was detected in 56.5%, S. pneumoniae in 22.5%, and Hib in 20.5% of the PCR-positive samples. Among N. meningitidis-positive CSF samples, 42.7%, 31.1%, 2.2%, and 0.7% belonged to serogroups W-135, B, Y, and A, respectively. This study highlights the emergence of serogroup W-135 disease in Turkey and concludes that vaccines to prevent meningococcal disease in this region must provide reliable protection against this serogroup.
Keywords: W135 Meningococcal Disease; Influenzae Type-B; Neisseria-Meningitidis; Children; Epidemiology; Carriage; England; Vaccine; Burden